ANALISIS KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH DASAR - Wendelinus Dasor, Yohanes (JIPD (Jurnal Inovasi Pendidikan Dasar), 2024)
This article highlights the importance of creating a positive work environment in elementary schools as a key to enhancing teacher productivity and well-being. Strategies such as performance rewards, flexible working hours, effective communication, empowerment, recognition, and professional training are suggested as ways to achieve this. Principals play a crucial role in managing resources, motivating teachers, and fostering a supportive environment. In conclusion, this article provides practical guidance for principals who aim to improve educational quality through the development of a more supportive and positive work environment in elementary schools.